2006
DOI: 10.1532/hsf98.20061012
|View full text |Cite
|
Sign up to set email alerts
|

The Changes and Effects of the Plasma Levels of Tumor Necrosis Factor after Coronary Artery Bypass Surgery with Cardiopulmonary Bypass

Abstract: Cardiac surgery and CPB stimulate systemic inflammatory processes characterized clinically by changes in cardiovascular and pulmonary function. Significant morbidity is rare, but most patients undergoing CPB exhibit some degree of organ dysfunction due to activation of the inflammatory response. This study showed that there were no major clinical results of TNF-alpha and white blood cell level, C-reactive protein, and erythrocyte sedimentation rate after the operation, but in patients with a high level of TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
2
7
0
1
Order By: Relevance
“…Abacilar et al reported a positive correlation between TNF-α level and postoperative mediastinal drainage amount 2. We found a similar relationship between these two parameters in our study, although not statistically significant.…”
Section: Other Parameterssupporting
confidence: 82%
“…Abacilar et al reported a positive correlation between TNF-α level and postoperative mediastinal drainage amount 2. We found a similar relationship between these two parameters in our study, although not statistically significant.…”
Section: Other Parameterssupporting
confidence: 82%
“…The clinical relevance of CABGrelatedsystemic inflammation varies with patients and such inflammation may be accompanied by intermittent organ dysfunction and finally, multi-organ failure, including renal and pulmonary dysfunction. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, bir yandan IL-6 ve IL-8'in sekresyonunu arttırırken, diğer yandan nötrofil ve monositler için kemotaktik etki yaratmakta, ve böylece inflamasyonu arttırmakta-dır. 4 Proinflamatuar sitokinlerin kalp cerrahisi sonrasında görülen AF ile olan ilişkisi hakkında çeşitli çalışmalar yapılmış, ancak mutlak bir ilişki ortaya konulamamıştır. 2,5 Biz bu çalışmamızda TNF-α ile postoperatif dönemde görülen AF arasındaki iliş-kiyi araştırdık.…”
Section: Tnf-α Kalp Cerrahisi Sonrası Görülen Atriyal Fibrilasyon İçiunclassified